Family revolution : marital strife in contemporary Chinese literature and visual culture - Xiao, Hui Faye (Modern language initiative., 2014)
"As state control of private life in China has loosened since 1980, citizens have experienced an unprecedented family revolution--an overhaul of family structure, marital practices, and gender relationships. While the nuclear family has become a privileged realm of romance and individualism symbolizing the post-revolutionary "freedoms" of economic and affective autonomy, women's roles in particular have been transformed, with the ideal "iron girl" of socialism replaced by the feminine, family-oriented "Ïgood wife and wise mother." Problems and contradictions in this new domestic culture have been exposed by China's soaring divorce rate. Reading popular "divorce narratives" in fiction, film, and TV drama, Hui Faye Xiao shows that the representation of marital discord has become a cultural battleground for competing ideologies within post-revolutionary China. While these narratives present women's cultivation of wifely and maternal qualities as the cure for family disintegration and social unrest, Xiao shows that they in fact reflect a problematic resurgence of traditional gender roles and a powerful mode of control over supposedly autonomous private life.Hui Faye Xiao is assistant professor of modern Chinese literature and culture at the University of Kansas."An original and important contribution to the scholarship on Chinese culture in the post-Mao era with a breadth of perspective and depth of insight that few works have matched. A devastating critique of the social, economic, and cultural regendering of China in the reform era." -Jason McGrath, University of Minnesota"Insightfully manages to situate the chosen texts in relation to the larger contexts of ideological and socioeconomic changes." -Xueping Zhong, Tufts University"--